Effect of recurrent fires on soil nutrient dynamics in a tropical dry deciduous forest of Western Ghats, India. (3rd October 2018) - Verma, Satyam; Jayakumar, S.
ABSTRACT: The role of forest fires in the soil dynamics and global carbon cycle has not been comprehensively studied in tropical forests as the effects of fire on tropical forest soils can be extremely variable. This study was aimed to understand how repeated fires affect physical and chemical properties of soil in a tropical dry deciduous forest and alter soil fertility and health. The study was carried out in the dry deciduous forest of Mudumalai Tiger Reserve. Soil samples were collected from unburned (B0) to six-time burned (B6) plots. Samples were collected from each plot from three different depths viz. 0–10 (Top), 10–20 (Middle), and 20–30 cm (Bottom) and analyzed for soil physical and chemical properties. Soil pH, EC, WHC decreased with increasing fire frequencies while bulk density increased. Organic Carbon, Total N, and available P decreased with increasing fire frequencies whereas extractable K initially increased but decreased with the very high frequency of fires. NO3 − N slightly decreased with high fire frequencies but NH4 − N decreased significantly with increasing fire frequency. These results provide a new insight regarding the influence of repeated fires on soil that will be valuable to understand the effect of fire on the recovery of soils and nutrient dynamics.